Keabasahan Surat Kuasa Khusus Dari Luar Negeri Tanpa Nazegelen: Sebuah Desuetude - Hartono, Julienna; Nugraha, Xavier; Budisusanto, Eko (Hukum dan Masyarakat Madani, 2021)
The special power of attorney is a crucial thing in a lawsuit, but it is not considered. For example, many are not aware of the nazegelen requirement stipulated in SEMA7/2012 for special power of attorney made overseas. Therefore, this legal research will analyze nazegelen as a condition for the validity of a special power of attorney made overseas, as well as the legal consequences if these conditions are not met. Sources of law will be analyzed using a statute approach and a conceptual approach. In conclusion, the requirements for the validity of a special power of attorney made overseas are: 1) state clearly and specifically the use of the special power of attorney, 2) clearly and specifically mention the role of certain level of court to be used, 3) clearly states the relevant relative competence, 4) mentions the identity and position of the parties in detail, 4) Must be legalized by representatives of the Republic of Indonesia, and 5) nazegelen. Of these conditions, the conditions that many do not know are related to the obligation to carry out nazegelen. As a result, although these requirements have been regulated in SEMA 7/2012, the norms are not applied. This condition is called desuetude. Non-fulfillment of the nazegelen requirements should be cause the lawsuit to be unacceptable, a procedural exception can be filed, and the examination process that occurs is invalid.